Konsep Manajemen Pembelajaran Tahfidz Al-Qur’an Di Pondok Pesantren Al-Ghozali Curug Gunung Sindur Bogor - Manaf, Sofwan; Cholid, Nashiruddin; Rachmadianty, Nadia (Universitas Darunnajah Jakarta, Indonesia, 2022)
Learning management is a process of managing, which includes planning, organizing, implementing, and evaluating activities. Activities related to the process of learning students by involving various factors in it, in order to achieve educational goals and seek to improve the quality of education. This research uses descriptive qualitative research methods. The method used to collect data is through interviews, observation, documentation. The results showed that the planning of the Tahfidz Al-Qur'an learning program at the Al-Ghozali Islamic Boarding School Curug Gunung Sindur Bogor was carried out by selecting or determining the vision, mission, organizational goals and determining strategies, policies, projects, programs, procedures, methods, systems, budgets, and standards needed to achieve goals. And the evaluation of the Tahfidz Al-Qur'an learning program at the Al-Ghozali Islamic Boarding School, Curug Gunung Sindur, Bogor is carried out by conducting an assessment and at the same time making corrections if necessary so that what is being done by the relevant parties can be directed to the right path with the aim of achieving the goals that have been set. redrawn.